Variability of Rhodium(III)-Catalyzed Reactions of Aromatic Oximes with Alkenes - Trifonova, Evgeniya A.; Komarova, Alina A.; Chusov, Denis; Perekalin, Dmitry S. (Synlett, 2020)
Acetophenone oxime reacts with various alkenes in the presence of the rhodium catalyst [Cp*RhCl2]2 (2.5 mol%; Cp* = pentamethylcyclopentadienyl) and 1,1,1,3,3,3-hexafluoropropan-2-ol as an important cosolvent. Styrene, aliphatic terminal alkenes, and strained cyclic alkenes gave the corresponding substituted dihydroisoquinolines in yields of 50–99%. On the other hand, alkenes containing functional groups close to the double bond gave a variety of different products. The reactions of acetophenone oxime with styrene or dec-1-ene in the presence of the chiral catalyst [(C5H2tBu2CH2tBu)RhI2]2 provided the corresponding dihydroisoquinolines with improved regioselectivity but a low enantiomeric ratio (61:39 in both cases).
Keywords: C–H activation; rhodium catalysis; oximes; alkenes; isoquinolines